Surgical treatment of infective endocarditis in children with congenital heart disease - ProkopovуchL.; Truba, Y.; Siromakha, S.; Spysarenko, S.; Malysheva, T.; Lazoryshynetz, V. (Ukrainian Journal of Cardiovascular Surgery, 2017)
The current work presents the experience of surgical treatment of infective endocarditis (IE) in children with congenital heart disease (CHD). During the period from 2010 to 2017 in Amosov National Institute of Cardiovascular Surgery 23 children with IE and CHD were operated. The average age of patients was 11.5±5.8 years. The clinical diagnoses of the patients were: ventricular septal defect n=13 (56,5%), stenosis of the pulmonary artery n=1 (4,3%), VSD with SP n=2 (8,7%), aortic stenosis and subaortic stenosis n=3 (13,0%), tetralogy of Fallot n=3 (13,0%), coarctation of the aorta n=1 (4,3%%). The infectious agent was detected in 19 (82,6%) cases. Hospital mortality was 8,7% (2 patients). Complications during the postoperative period were observed in 10 (4351%) patients. During the late postoperative period 18 patients (85,7%) were examined. The average time of patients observation was 3,1±1,6 years. Symptoms of IE were returned in two clinical cases. After the reoperation cases of re-infection and mortality were not observed.